(untitled) (Marketing Journal, 2025)
This study analyzes the potential for improving retail efficiency in Central Asian countries through the implementation of CRM systems, use of customer data, loyalty programs, and omnichannel strategies. Rapid e -commerce growth, uneven digital 705 infrastructure, and dominance of cash payments were identified as key barriers to CRM practices. A customer segmentation approach based on the RFM -V model is proposed. Practical recommendations were developed to adapt CRM strategies to local conditions, im prove data quality, and digitize loyalty programs. The presented conceptual framework may support the competitiveness of retail chains in developing markets.